Biosynthesis of very long-chain fatty acids (C > 24) in Atlantic salmon: Cloning, functional characterisation, and tissue distribution of an Elovl4 elongase - Carmona-Antonanzas, Greta; Monroig, Oscar; Dick, James R; Davie, Andrew; Tocher, Douglas R (Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, 2011)
The elongases of very long-chain fatty acids (Elovl) account for the rate-limiting condensation step of the elongation process in fatty acid (FA) biosynthesis in vertebrates. One member of the Elovl family, Elovl4, has been regarded as a critical enzyme in vertebrates in the production of the so-called very long-chain fatty acids (VLC-FA), a group of compounds that have been scarcely explored in fish. Here we report on the cloning of a novel elovl4-like elongase from Atlantic salmon. The salmon elovl4 cDNA codes for a putative protein containing 306 amino acids. Heterologous expression in yeast demonstrated that salmon Elovl4 efficiently elongated saturated FAs up to 36:0, with 24:0 and 26:0 appearing as preferred substrates. Additionally, salmon Elovl4 effectively converted C20 and C22 polyunsaturated fatty acids to elongated polyenoic products up to C36. Tissue distribution showed that elovl4 mRNA transcripts are abundant in eye, brain and testes, suggesting that, as described in mammals, these tissues are important metabolic sites for the biosynthesis of VLC-FA. Our results are discussed in comparison with the functional analyses observed in Elovl4 proteins from other vertebrates, and also other Elovl proteins investigated previously in Atlantic salmon.